2000
DOI: 10.1111/j.1499-1654.2000.001522.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Epilepsy With Occipital Paroxysms: Clinical Variants in134 Patients

Abstract: The most common type of CEOP, the Panayiotopoulos type, is characterized by a cluster of signs and symptoms sufficiently delineated to justify their separate classification from Gastaut-type CEOP, despite the absence of ictal vomiting in more than 50% of the patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Moreover, occipital paroxysms are a nonspecific electroencephalographic manifestation observed in many epileptic and nonepileptic disorders. They are morphologically similar to the abnormalities observed in BECTS, the main difference being that the waves occur in the occipital rather than in the centrotemporal regions [7] . As in BEI, subclinical cortical hyperexcitability in healthy children (without associated clinical recognizable seizures) may migrate to different brain areas as an expression of maturation, though no studies that have yet provided conclusive data exist, suggesting that this migrating hyperexcitability is age-related.…”
Section: Introductionsupporting
confidence: 72%
“…Moreover, occipital paroxysms are a nonspecific electroencephalographic manifestation observed in many epileptic and nonepileptic disorders. They are morphologically similar to the abnormalities observed in BECTS, the main difference being that the waves occur in the occipital rather than in the centrotemporal regions [7] . As in BEI, subclinical cortical hyperexcitability in healthy children (without associated clinical recognizable seizures) may migrate to different brain areas as an expression of maturation, though no studies that have yet provided conclusive data exist, suggesting that this migrating hyperexcitability is age-related.…”
Section: Introductionsupporting
confidence: 72%
“…Most clinicians treat seizures with CBZ or VPA. [ 12 13 14 ] García and Rubio[ 15 ] reported that LEV used in three children with PS type. They found efficacy on seizure control in PS.…”
Section: Discussionmentioning
confidence: 99%
“…While vomiting has been cited to occur as the initial event in 60-80% (Lada et al 2003Koutroumanidis, 2002, Panayiotopoulos, 2001, Oguni et al 1999, others have reported a frequency of only 44% (Kivity et al 2000). Vomiting is accompanied or followed by tonic eye, and less commonly head, deviation in 70-98% (Oguni et al 1999, Caraballo et al 2000.…”
Section: Clinical Manifestations Of Panayiotopoulos-type Bceopmentioning
confidence: 99%
“…Fixation-off sensitivity (FOS), the occurrence of interictal discharges as the result of elimination of central vision and fixation, is a feature of both types of BCEOP (Panayiotopoulos, 1989, Panayiotopoulos, 1998a. Fixation-off sensitivity occurs less commonly in other conditions as compared to BCEOP (Kivity et al 2000. Panayiotopoulos, 1998a.…”
Section: Eeg Findings In Bceopmentioning
confidence: 99%
See 1 more Smart Citation